Bioethics and Science (The Hastings Center report, 2018)
Bioethics comes in for furious criticism in Stephen Pinker's new book, Enlightenment Now. Pinker argues that scientists are making human lives better and better, and that lives would get still better even faster if bioethicists did not use ideas like informed consent, dignity, sacredness, and social justice to hobble the scientists. Daniel Callahan, a cofounder of The Hastings Center and arguably of bioethics, is perhaps the best living embodiment of a bioethicist who has written about medical progress, and the March-April 2018 issue of the Hastings Center Report turns to him for a review of Pinker's book. In his essay, Callahan describes bioethics as guiding science, addressing problems generated by scientific developments and attempting to head off possible problems, rather than as broadly opposing science. That description of bioethics serves as well as anything to convey the flavor of much of this issue of the Report.